PENGARUH ELECTRONIC WORD OF MOUTH DALAM ONLINE REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE XIAOMI (Survei Pada Followers Instagram @erafonestores) - Mohamad Septiawan Evriyanto, (2022)
This research aims to discuss electronic word of mouth in an online review of purchasing decisions for Xiaomi smartphone products, using the theory of individual differences. The method used in this research is quantitative explanatory by using primary data sources in the form of a questionnaire as the research instrument. The population of this study is Instagram followers @erafonestores, the sampling technique is carried out using a non-probability sampling technique with a purposive sampling method, because the sample is selected according to the criteria that have been determined to take part in the survey held. Researchers used the stages of validity and reliability testing to test the questionnaire instrument that had been made. Stages of data analysis using correlation test, coefficient of determination test, regression test, and hypothesis testing. The data testing technique was carried out with the SPSS 20 program. The result of this research indicate that the correlation of variable X to variable Y has a strong relationship with a correlation value of 0.799. Based on the results of the calculation of the coefficient of determination, it shows that the influence caused by Electronic Word of Mouth in the Online Review on the Purchase Decision of Xiaomi Smartphone products is 82%, while the rest can be influenced by other factors. Then for the results of the hypothesis test, namely Ho is rejected and Ha is accepted, which means that there is an influence of electronic word of mouth in online reviews on purchasing decisions for Xiaomi smartphone products.